3
$\begingroup$

Does the following apply? $$P(A\mid B)=P(A)\implies P(\neg A\mid B)=P(\neg A)$$

My rough answer is that suppose $A$ is the probability of rainy and $B$ is the probability of toothache. Then both $P(A\mid B)=P(A)$ and $P(\neg A\mid B)=P(\neg A)$ apply. But can we prove this mathematically?

$\endgroup$
7
$\begingroup$

$𝑃(¬𝐴|𝐵)$

= $1 - 𝑃(𝐴|𝐵)$

= $1 - 𝑃(𝐴)$, from given $P(A|B) = P(A)$

= $𝑃(¬𝐴)$, Q.E.D.

$\endgroup$
0
3
$\begingroup$

Firstly, $$p(A|B)=p(A)\implies \frac{p(A\cap B)}{p(B)}=p(A)\implies p(A\cap B)=p(A)p(B)$$ Then, $$p(A'|B)=\frac{p(A'\cap B)}{p(B)}$$ $$=\frac{p(B)-p(A\cap B)}{p(B)}$$ $$=1-\frac{p(A)p(B)}{p(B)}$$ $$=1-p(A)=p(A')$$

$\endgroup$
0

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.